2023
DOI: 10.1021/acsnano.3c06103
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Immunomodulatory Stents Using Zinc Ion–Lysozyme Nanoparticle Platform for Vascular Remodeling

Bo Zhang,
Huining Wan,
Xiyu Liu
et al.

Abstract: Rapid endothelialization of cardiovascular materials can enhance the vascular remodeling performance. In this work, we developed a strategy for amyloid-like protein-assembly-mediated interfacial engineering to functionalize a biomimetic nanoparticle coating (BMC). Various groups (e.g., hydroxyl and carboxyl) on the BMC are responsible for chelating Zn 2+ ions at the stent interface, similar to the glutathione peroxidase-like enzymes found in vivo. This design could reproduce the release of therapeutic nitric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In recent years, the eNOS/cGMP/PKG signal pathway has been considered an important target for therapies such as regulating blood pressure, attenuating IR injury, and delaying heart failure ( Anwar et al, 2017 ; Kolijn et al, 2021 ; Park et al, 2022 ). Additionally, the eNOS/cGMP/PKG signal route is crucial for controlling blood pressure and vascular endothelial function ( Zhang et al, 2023 ).…”
Section: Cardiovascular Disease-related Signal Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the eNOS/cGMP/PKG signal pathway has been considered an important target for therapies such as regulating blood pressure, attenuating IR injury, and delaying heart failure ( Anwar et al, 2017 ; Kolijn et al, 2021 ; Park et al, 2022 ). Additionally, the eNOS/cGMP/PKG signal route is crucial for controlling blood pressure and vascular endothelial function ( Zhang et al, 2023 ).…”
Section: Cardiovascular Disease-related Signal Pathwaysmentioning
confidence: 99%
“…In recent years, the eNOS/cGMP/PKG signal pathway has been considered an important target for therapies such as regulating blood pressure, attenuating IR injury, and delaying heart failure (Anwar et al, 2017;Kolijn et al, 2021;Park et al, 2022). Additionally, the eNOS/cGMP/PKG signal route is crucial for controlling blood pressure and vascular endothelial function (Zhang et al, 2023). Li et al (2015) found in an experimental model of myocardial ischemia-reperfusion (MIR)in rats that SCU was able to exert an anti-MIR injury effect by increasing the levels of p-VASP Ser239 in rat cardiac tissue and serum.…”
Section: Enos/cgmp/pkg Signal Pathwaymentioning
confidence: 99%